(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article explores inclusive education as a social phenomenon within the broader framework of the education and upbringing process. It examines the significance of inclusive practices in fostering equality, social integration, and the holistic development of all learners, including those with special needs. The study reflects on how inclusive education contributes to social cohesion and equity, especially in the context of Uzbekistan’s educational reforms. By analyzing the principles and implementation of inclusive education, the article highlights the challenges and opportunities that arise in its integration into the general education system. It underscores the importance of teacher preparedness, institutional support, and community involvement in ensuring the success of inclusive practices.